Muslim empowerment in Ghana: analysing the spectrum of Muslim social mobilization during the Internet age - Weiss, Holger (Islam in Africa, 2024)
"This book is the first 'groundwork' on Muslim NGOs in contemporary Ghana. It builds upon a database of more than 600 Muslim non-profit associations, foundations and grass-roots organisations whose activities are traced through extensive use of social media. The first part of the book scrutinises the varieties of their activities and operational spaces, their campaigns and target groups, alongside their local, regional, national and international connections. The second part analyses contemporary debates on infaq, sadaqa, waqf and zakat as well as Islamic banking and micro-finance schemes for promoting social welfare among Muslim communities in Ghana"--